Pemberdayaan melalui Pertemuan Peningkatan Kemampuan Keluarga (P2K2) di Kecamatan Karawaci Kota Tangerang bagi Keluarga Penerima Manfaat (KPM) - Triano, Habibah Mutiara; Machdum, Sari Viciawati (LP2M INSURI Ponorogo, 2023)
The Family Hope Program (PKH) is a national priority to accelerate poverty reduction. One of the PKH Beneficiary Families' (KPM) obligations to improve this is to attend Family Capacity Building Meetings (P2K2). This study aims to describe the empowerment of KPM PKH through P2K2 in the Karawaci sub-district. The method used in this research is a qualitative method with a descriptive research type. Data collection techniques are through in-depth interviews, observation, and document study. The study results show that empowerment through P2K2 for KPM in the Karawaci sub-district has been going well, but until now, there has been no independent graduation of KPM PKH due to P2K2. PKH assistants obstacles in empowering KPM PKH through P2K2, namely the participation and level of understanding of KPM. For this reason, the ability and number of assistants, P2K2 operational funds, facilities, and P2K2 module materials need attention to maximize self-graduation efforts, especially comprehensive attention related to economic aspects in empowering KPM.